Digitization of the Arabic manuscript in the light of artificial intelligence technologies-from preservation to investment - KERKOURI, Rokia (The International tax journal, 2026)
This study aims to highlight the role of digitization and artificial intelligence technologies in the maintenance and preservation of the Arabic manuscript, and to move it from just a preserved heritage vessel to a knowledge resource amenable to scientific and cultural investment. It seeks to show how modern digital technologies have contributed to the transformation of Arabic manuscripts into indexable materials, search, and automated analysis, which opens up new horizons for their reuse in scientific research and inter-related studies. The study also highlights the most prominent challenges that hinder this transformation, such as weak digital infrastructure, lack of specialized competencies, and the dispersion of manuscripts between different institutions and groups. It proceeds from a central problem: How can digitization technologies and artificial intelligence go beyond the logic of traditional preservation, and contribute to the investment of the Arabic manuscript as an active element in contemporary knowledge. The study concludes that the adoption of clear institutional policies, the promotion of specialized training programs, and the use of artificial intelligence tools in the digital processing of manuscripts are key pillars to ensure the sustainability of this heritage and achieve a real transition from conservation to knowledge investment.